Theory of planned behaviour and readiness for changes: implication for organisations - Ogbodoakum, Nnamdi; Abiddin, Norhasni Zainal (UPI Press, 2017)
An organisation’s long term survival in today’s challenging environment will depend on constant adaptation to changes in the environment. The majority of behavioural theories acknowledged individual as the central focus. Certain environmental or situational factors and applicable change-related processes have been recognised and studied as having significant influence in determining individual, group, and organisational behaviours. In the context of readiness for change, the theory of planned behaviour would be suitable in assessing the change supporting attributes of employees in achieving a strong readiness for change status. The connection between the theory of planned behaviour and individual readiness for change is that if a person has positive evaluation of change effort (attitude), supported by his close peers (subjective norm), and is confident that such change efforts will be undertaken successfully (perceived behavioural control), there will be improved motivation (intention) to actually engage in the change effort (readiness for change). This paper will discuss the Theory of Planned Behaviour and the readiness for change in organizations.